Notifying a patient of actions taken as an element of informed consent - Zurzycka, Patrycja (Nursing Problems / Problemy Pielęgniarstwa, 2014)
Progressive social changes and development in the biomedical sciences has caused patients taking part in a therapeutic process to demand comprehensive and comprehensible information about the services offered. Only full and complete access to all information pertinent to a therapeutic process will allow a patient to decide and agree on the activity proposed. This study is aimed at discussing the patient’s rights to information and the description of conscious consent. The work discusses the criteria for conscious consent and analyses legal and ethical standards regarding the obligation of information and obtaining a patient’s consent to health services. Emphasis is laid upon adult patients, capable of understanding information and giving their consent. Nursing Topics 2014; 22 (1): 113–118